Comparison of Methodologies for the Behavior Factor Estimation in Seismic Design of Buildings: Case Study of Geo-Sourced Masonry Construction - Noura Zarzour; Maria Paola Santisi d’Avila; Andrea Penna; Luca Lenti; Michel Oggero (Buildings)
The behavior factor, which represents the force reduction that a structure would experience if its response was completely elastic compared with the seismic forces used for design, is defined in seismic design codes for common construction techniques and materials. A specific assessment is needed when novel construction materials are adopted. The lack of accurate structural performance estimations limits the use of green construction materials because building codes only allow the use of minimum values for the behavior factor. This research aims to verify the reliability of the proposed capacity-demand-based (CDB) method for the estimation of the force reduction factor and behavior factor, by comparison with other procedures such as demand-based, capacity-based and formula-based approaches. The main characteristic of the proposed approach is that the ductility-FRF curve is obtained numerically for the building natural period, instead of imposing an analytical FRF-ductility-period relationship. The advantage of the CDB-method is its efficiency from a computational point of view without restrictions concerning the construction material and structural typology. The results are compared in the case where dynamic analyses are performed for a three-dimensional (3D) building model (considered as a reference) and for an equivalent single-degree-of-freedom system which reduces the computation time. The CDB-method yields safe results compared with the N2 method, and it is consistent with a capacity-based approach applied to the 3D building model.